"Ikke uden min datter" - Analyse af populærorientalisme i vestlige medier - Berg, Magnus (Kvinder, Køn & Forskning, 2000)
The article analyzes the bestseller by Betty Mahmoody "Not without my Daughter". By using traditional theories within the field of orientalism, the author shows different aspects of Western constructions of the Orient. This more popularized form of orientalized writing has the same cultural function as can be said of "high art", and is in this article related to discussions of modernity and gender within Western societies.